Sosialisasi Penerapan Aplikasi Smart RT Membantu Pemantauan Covid-19 Di Kelurahan Manukan Kulon, Kecamatan Tandes, Kota Surabaya - Tjatursari Widiartin; Kukuh Primananda Putra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
Many Indonesians have been exposed to the corona virus (COVID-19). COVID-19 itself first occurred in the city of Wuhan, the capital of China's Hubei province and has since spread globally, [1]. The Indonesian people need information in the form of monitoring the spread of COVID-19 in real-time. For now, the technology that can be achieved by all and the most widely used is web-based. need the web to find information about COVID-19 cases from various accurate sources. After entering data into the website, people can use it, the Smart RT web runs in real-time. in several trials that will be carried out by the RT 13 community, namely by using the site as a means of COVID-19 information, and the RT 13 community tends to be able to anticipate the spread of COVID-19